Uji Berbagai Konsentrasi Konidia Beauveria bassiana (Balls) Vuill Terhadap Mortalitas Hama Putih Palsu (Cnaphalocrocis medinalis (Guenee)) pada Tanaman Padi (Oryza sativa L.) - Sain Muhammad Alfian; Noor Laili Aziza; Jumar Jumar (Agroekotek View, 2021)
One of the biological obstacles faced in conducting rice farming is the presence of fake white pests. False white pests (C. medinalis) are potential pests, because the symptoms of false white pests are quite high and are often found in rice plants. These pests usually cause significant yield losses, especially on land that is over-fertilized and planted during the rainy season (Surtikanti, 2011). One of the efforts to deal with these pests is to use the biological agent Beauveria bassiana. B. bassiana is an entomopathogenic fungi that are environmentally friendly, cheap and easy to produce. The purpose of this study was to determine the effect of applying various concentrations of B. bassiana conidia on the mortality of false white pests (C. medinalis) and to determine the most effective concentration in increasing mortality of false white pests (C. medinalis). This study used a randomized block design (RBD) method with single factor treatment in the form of various concentrations of B. bassiana conidia which consisted of five treatments, namely b0: control (no treatment), b1: conidia concentration of B. bassiana 1x 104 conidia.ml-1, b2: conidia concentration B. bassiana 1x 106 conidia ml.-1, b3: conidia B. bassiana concentration 1x 108 conidia ml.-1 and b4: conidia B. bassiana concentration 1x 1010 conidia ml.-1. The results showed that testing various concentrations of B. bassiana conidia had no effect on mortality of false white pests (C. medinalis). The highest percentage of mortality against false white pests (C. medinalis) is only 12.5%, so there is no concentration that is most effective in increasing the mortality of false white pests (C. medinalis).